(untitled) (American Journal of Islam and Society, 2005)
This compilation of Ismaili literature is the result of over thirty years of research, put together by one of the world’s leading experts on Ismaili thought and history. Previous attempts to take account of Ismaili literature have been carried out by such noteworthy scholars as W. Ivanow and I. Poonawala. But as the author notes, their compilations were essentially inventories of manuscripts, whereas the present bibliography is solely concerned with those materials, both primary sources and secondary studies, which have been published. This bibliography contains an important survey of medieval and contemporary developments in Ismaili studies. Particular attention is paid to the early polemical assaults (and many outright fabrications) to which the Ismaili image collectively fell victim and which caused numerous misunderstandings concerning key Ismaili doctrines. Particularly noteworthy in this regard is the Ismaili “black legend” that surreptitiously came to the fore by the tenth century CE (see p. 87). This image, which severely distorted Ismaili teachings with regard to both its faith and practice, resulted in increased Ismaili polemics and hostilities. In addition, this image also suffered defamation from outside the house of Islam, for distortions spread by the Crusaders and other European travelers resulted in a slew of embellished tales – the “Assassin legends.” ...